Проектування інформаційної системи дистанційного вивчення іноземних мов з методами гейміфікації - Басюк, Тарас; Плебанський, Микола (Видавництво Львівської політехніки, 2025)
In the article, the authors present the features of designing an information system for distance foreign language learning with integrated gamification elements. The analysis of existing educational systems is provided, their shortcomings are highlighted, and the functionality of the proposed system is justified. The system design was carried out using a structural approach and the IDEF0 methodology. The results of the design and the features of information flows within the developed system are described.
Keywords: гейміфікація; дистанційне навчання; інформаційна система; IDEF0